Awareness and preparedness of human monkeypox outbreak among university student: Time to worry or one to ignore? - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Naseem Mohammed Abdulla; Faris El-Dahiyat; Moyad Shahwan; Nageeb Hassan; Obaida Jairoun, Dr; Nuha Ghazi Alyousef; Safia Sharif; Ammar Ali Saleh Jaber (Elsevier, 2022)
Background: The growing number of human monkeypox cases worldwide illustrates the importance of early detection, prevention, management and quick action from healthcare authorities. The WHO confirmed a hundred of Monkeypox cases worldwide and disclosed Monkdypox as a worldwide emergency situation Objectives: To assess the knowledge about human monkeypox' source, signs/symptoms, transmission, prevention and treatment among Al Ain university students in the UAE. Methods: This descriptive cross-sectional study aimed to assess Al Ain University students' knowledge of Human Monkeypox. A validated questionnaire was distributed to students between lectures. The respondents' knowledge of human Monkeypox was assessed by 21 questions that examined the participants' knowledge of Monkeypox as follows: 5 items examined knowledge of the source, definition, and incubation time; 2items assessed the mechanism of transmission of human Monkeypox, 7 items assessed the signs and symptoms; 7 items assessed the preventative measures; and 6 items assessed the treatment modalities. A multivariate logistic regression model was used to identify the factors influencing respondents' knowledge of human Monkeypox among university students. Results: A total of five hundred and fifty-eight (558) students participated in the study. The average knowledge score was 70.1%, with a 95% confidence interval (CI) of 68.9 − 71.3. Of the total participants, 111 (19.9%) had poor knowledge about human Monkeypox, 320 (57.3%) had moderate knowledge, and 127 (22.8%) had good knowledge. The results of the statistical modelling showed that Old age (OR 0.681; 95% CI 1.005-1.016), female gender (OR 1.26; 95% CI 0.813 -0.961), participants from medical colleges (OR 1.22; 95% CI 1.13 -1.32) having a history of human chickenpox infection (OR 2.6; 95% CI 2.3-2.9) and receiving information on human Monkeypox during education (OR 1.14; 95% CI 1.05-1.2) were strong determinants for good knowledge about human Monkeypox. Conclusion: knowledge of Monkeypox among the participants is relatively low, particularly regarding the epidemiology, symptoms and treatments. Therefore, increasing knowledge of Monkeypox will be key to enhancing the capacity to respond to human monkeypox cases and to relay pertinent data to a disease surveillance system.